Economy-wide carbon emissions pinch analysis - Tan, Raymond Girard R. (Animo Repository, 2017)
Carbon Emissions Pinch Analysis (CEPA) was first introduced for carbon-constrained energy planning purposes. Since its inception, CEPA has been modified to apply to various systems at different scales, utilized in different geographic contexts, and extended through the use of alternative sustainability metrics or footprints. In this paper, CEPA is further extended to economy-wide systems where the segments of composite curves are comprised of sectors in a national or regional economy. This approach uses input output analysis (IOA) to calculate carbon footprints of major sectors per unit of economic value; these are then subjected to pinch analysis using established CEPA methodology. The methodology is shown to yield important insights for carbon management by means of a case study using Philippine statistical data. © 2017, AIDIC Servizi S.r.l.